Zagadnienie charakteru prawnego stowarzyszeń jednostek samorządu terytorialnego - Blicharz, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Although the legal character of associations of self-government units is disputable, it is beyond any doubt that they represent the organisational and legal form which usually complements the activity of self-government. They serve in particular way to support the idea of self-government within the area of performing of public tasks.
Keywords: stowarzyszenia; jednostki samorządu terytorialnego